2022
DOI: 10.2340/actadv.v102.1128
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Risk Factors for Dupilumab-associated Ocular Surface Disease in Patients with Atopic Dermatitis

Abstract: This study identified risk factors for the development of dupilumab-associated ocular surface disease in patients with moderate-to-severe atopic dermatitis in a large prospective daily practice cohort. Data from the Dutch BioDay Registry were used to assess the risk of developing dupilumab-associated ocular surface disease, by performing univariate and multivariate logistic regression analyses. A total of 469 patients were included, of which 152/469 (32.4%) developed dupilumab-associated ocular surface disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…We previously identified risk factors for developing DAOSD in patients with moderate-to-severe AD (n = 469). 32 Self-reported DAOSD was found in 152/469 (32.4%) patients, and univariate analyses showed an association between eyelid eczema in the past year and developing DAOSD, which was also found by Touhouche et al 12 This raises the question whether patients with pre-existing OSD are predisposed to developing DAOSD. In the above-mentioned study including 469 AD patients, it was reported that having a history of any eye disease (excluding self-reported allergic conjunctivitis) requiring ophthalmic medication before starting dupilumab treatment is a risk factor for developing self-reported DAOSD.…”
Section: Risk Factors For Developing Daosdmentioning
confidence: 71%
See 2 more Smart Citations
“…We previously identified risk factors for developing DAOSD in patients with moderate-to-severe AD (n = 469). 32 Self-reported DAOSD was found in 152/469 (32.4%) patients, and univariate analyses showed an association between eyelid eczema in the past year and developing DAOSD, which was also found by Touhouche et al 12 This raises the question whether patients with pre-existing OSD are predisposed to developing DAOSD. In the above-mentioned study including 469 AD patients, it was reported that having a history of any eye disease (excluding self-reported allergic conjunctivitis) requiring ophthalmic medication before starting dupilumab treatment is a risk factor for developing self-reported DAOSD.…”
Section: Risk Factors For Developing Daosdmentioning
confidence: 71%
“…In the above-mentioned study including 469 AD patients, it was reported that having a history of any eye disease (excluding self-reported allergic conjunctivitis) requiring ophthalmic medication before starting dupilumab treatment is a risk factor for developing self-reported DAOSD. 32 Katsuta et al also found that AD patients with DAOSD were more likely to have a history of ocular complications, suggesting that patients who develop DAOSD may already have an (undiagnosed) ocular disease that possibly worsens during treatment with dupilumab. 33,34 Taken together, pre-existing ocular pathology (e.g., especially when requiring ophthalmic medication or eyelid eczema) may be associated with developing DAOSD.…”
Section: Risk Factors For Developing Daosdmentioning
confidence: 98%
See 1 more Smart Citation
“…Conjunctivitis is a well-known side effect of the medication, occurring in up to a third of patients, with onset typically occurring approximately 6 weeks into therapy. Risk factors for development include a prior history of ocular surface disease and severe atopic dermatitis at baseline [28 ▪▪ ,29]. Treatment should be initiated with artificial tears and consideration for corticosteroid eye drops.…”
Section: Dupilumab-induced Conjunctivitismentioning
confidence: 99%
“…Conditions were selected based on relevance, relative urgency, and recent advances in their etiologic/therapeutic understanding. A more detailed evaluation of associations can be found in the online supplementary material of this article (Supplementary Tables 1-3, http://links.lww.com/MOP/A66) [8,14,18,29,30]. An overview of ocular anatomy and associated disease states is included (Fig.…”
Section: Introductionmentioning
confidence: 99%